Islamic Education Management in the Framework of the Philosophical Trilogy - Nurazizah, Efa (Journal of Islamic Thought and Philosophy, 2025)
This study discusses Management Development in Islamic Educational Institutions. The application of management in Islamic educational institutions will not distance education from Islamic values; instead, its presence makes Islamic education more organized, planned, and able to achieve educational goals effectively. Management development in Islamic educational institutions is carried out through a philosophical approach within the framework of ontology, epistemology, and axiology. Development through this philosophical framework is expected to enable Islamic Educational Management to continue moving towards its ideal form in line with the dynamic development of science and technology. Islamic educational institutions are not merely places for transferring religious knowledge; moreover, Islamic educational institutions must be able to produce a generation capable of competing amidst the development of science and technology. This is proof that Islam is rahmatan lil'alamin (blessing for all the universe), whose existence is timeless.